Child sedation in Dentistry for patients with disabilities (Research, Society and Development, 2024)
Objectives: Given the difficulty and high demand for dental care for children with disabilities, the aim of this review is to analyze the literature regarding the techniques and sedative substances most commonly used and available for managing pediatric dental care. Methodology: For this study, a search was conducted in the databases of Bireme, Scielo, and PubMed using the descriptors "children with disabilities," "conscious sedation," "pediatric dentistry," "conscious sedation," "disabled patients," "sedation," "pediatric dentistry," "children with disabilities" associated with the boolean operator AND. The articles selected for this study were those published between 2015 and 2024 and of greater relevance. Results and Discussion: Overall, based on the analyzed studies, sedation is a technique that yields good results in pediatric patients with disabilities. Nitrous oxide, due to its characteristics, has been suggested as a good alternative to general anesthesia. Among benzodiazepines, midazolam has better pharmacokinetics and acceptance. Conclusion: Treating a child with a disability is challenging, emphasizing the need for knowledge and greater professional readiness among dentists and the involved team.